The aging workforce handbook : individual, organizational, and societal challenges - Antoniou, Alexander-Stamatios G.; Burke, Ronald J.; Cooper, Cary L. (Emerald Group Publishing Limited, 2016)
This volume critically reviews the phenomenon of the aging workforce, adopting an interdisciplinary perspective that examines the challenges raised on an individual, organizational and societal level. Core issues framing the concept of the aging workforce and its consequences are presented by a team of leading contributors from around the world. Despite the visible trend towards a much older global population and workforce, research on the aging workforce, employment and retirement is in its infancy and faces a range of paradoxes. Taking under consideration all the challenges, ranging from the microenvironment of the individual level (individual, family, friends) to the organizational and macro-environment of the society (infrastructure, services, legislations etc.), this is an essential resource for policymakers and organizations designing strategies to address the challenge of the ageing society. Scholars, graduates and researchers in occupational and health psychology, human resources, business and management, as well as sociology, will gain a better understanding of the changing trends in the characteristics of the workforce through this multi-level review.- Resumé vydavatel
Keywords: senioři; age management; personální management; zaměstnanost; older people; personnel management; employment; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals